A remote and cost‐optimized voting system using blockchain and smart contract. Issue 1 (5th January 2023) - Neloy, Mohammad Nabiluzzaman; Wahab, Md. Abdul; Wasif, Sheikh; All Noman, Abdulla; Rahaman, Mustafizur; Pranto, Tahmid Hasan; Haque, A. K. M. Bahalul; Rahman, Rashedur M.
Abstract: Traditional voting procedures are non‐remote, time‐consuming, and less secure. While the voter believes their vote was submitted successfully, the authority does not provide evidence that the vote was counted and tallied. In most cases, the anonymity of a voter is also not sure, as the voter's details are included in the ballot papers. Many voters consider this voting system untrustworthy and manipulative, discouraging them from voting, and consequently, an election loses a significant number of participants. Although the inclusion of electronic voting systems (EVS) has increased efficiency; however, it has raised concerns over security, legitimacy, and transparency. To mitigate these problems, blockchain technology has been leveraged and smart contract facilities with a combination of artificial intelligence (AI) to propose a remote voting system that makes the overall voting procedure transparent, semi‐decentralized, and secure. In addition, a system that aids in boosting the number of turnouts in an election through an incentivization policy for the voters have also developed. Through the proposed virtual campaigning feature, the authority can generate a decent amount of revenue, which downsizes the overall cost of an election. To reduce the associated cost of transactions using smart contracts, this system implements a hybrid storage system where only a few cardinal data are stored in the blockchain network. Abstract : A remote voting system is proposed with the blockchain and smart contract based technology with a combination of Artificial Intelligence technique. To reduce the associated cost of transactions using smart contracts, our system implements a hybrid storage system where only a few cardinal data is stored in the blockchain network.